STRATEGI KEBIJAKAN LUAR NEGERI TUVALU: UPAYA MENGHADAPI KRISIS IKLIM DAN ANCAMAN EKSISTENSIAL NEGARA: CONFRONTING THE CLIMATE CRISIS AND THE COUNTRY’S EXISTENTIAL THREAT - Aninda Nuraygy Hajjisa; Charisya Charisya (Intermestic: Journal of International Studies, 2025)
This study analyzes Tuvalu’s foreign policy as a Small Island Developing State (SIDS) facing the existential threat of the climate crisis. Using Constructivism, Small State Theory, and Climate Diplomacy, this qualitative case study examines COP26–COP29 (2021–2024) documents to explore how Tuvalu transforms its “most vulnerable state” identity into normative bargaining power. The findings show that Tuvalu leverages moral pressure, symbolic acts, identity framing, and the AOSIS network to (1) secure the 1.5°C target in the Paris Agreement, (2) advocate for the Loss and Damage Fund, and (3) push for a US$300 billion annual increase in global climate finance through the New Collective Quantified Goal. Tuvalu’s strategy illustrates how small states, despite limited resources, can shape global norms and policy outcomes. This study contributes to international relations scholarship by highlighting the role of identity, norms, and moral authority in contemporary climate diplomacy.